International market success among smaller agri-food companies: some case study evidence - Ibeh, Kevin I.N.; Ibrahim, Essam; Panayides, Photis (My University, 2006)
Purpose - The paper aims to explore the relevance of key marketing concepts, including market orientation, marketing competencies and resources, and competitive marketing strategies, in explaining international market success among smaller agri-food companies. Design/methodology/approach - The paper presents a multi-case research, involving five small to medium-sized enterprises (SMEs), from different agri-food sub-sectors. The research employed a semi-structured interview guide, and subjected the generated data to meaning-oriented content analysis procedure. Findings - Evidence points to the influential impact of adopting a marketing orientation; developing advantage-generating competencies in the product, channel and relationship management areas; leveraging strategically-relevant managerial, production and brand/reputational resources; and deploying appropriate competitive marketing strategies. Research limitations/implications - Limitations and implications of the research generally relate to the use of a small, non-representative sample and the less than robust specification of the major constructs explored in the study. Future researchers should strive to obtain larger samples, develop a set of relevant hypotheses and test same using appropriate statistical techniques. Originality/value - Findings offer a set of important lessons for smaller agri-food companies and policy makers seeking to improve performance levels in international markets. They also add to the limited body of knowledge on the key influences on international marketing success within the agri-food sector
Keywords: International business; Farm produce; Great Britain; Agriculture; Business enterprises